2017
DOI: 10.1002/lary.26983
|View full text |Cite
|
Sign up to set email alerts
|

Absence or mislocalization of DNAH5 is a characteristic marker for motile ciliary abnormality in nasal polyps

Abstract: NA. Laryngoscope, 128:E97-E104, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Recently, we have identified mislocalization and altered expression of DNAH5, the critical cilia structural protein, in patients with chronic rhinosinusitis with nasal polyps, suggesting their possible contribution to impaired mucociliary clearance [7]. In this study, we expanded our investigation to the assessment of FOXJ1, a critical ciliogenesis marker, to determine whether the altered expression or localization of FOXJ1 was associated with AR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have identified mislocalization and altered expression of DNAH5, the critical cilia structural protein, in patients with chronic rhinosinusitis with nasal polyps, suggesting their possible contribution to impaired mucociliary clearance [7]. In this study, we expanded our investigation to the assessment of FOXJ1, a critical ciliogenesis marker, to determine whether the altered expression or localization of FOXJ1 was associated with AR.…”
Section: Discussionmentioning
confidence: 99%
“…We referred to the criterion from Shoemark et al [17] and our previously published study [7]. That is, samples with more than 7 out of 10 ciliated cells (70%) clearly labeled with cilia markers would be considered normal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…that aid in the proper function of the motile cilia in the airways are aberrantly expressed in ciliated airway epithelial cells which are the major target for RV infection (Griggs et al, 2017). Such form of secondary cilia dyskinesia appears to be present with chronic inflammations in the airway, but the exact mechanisms are still unknown (Peng et al, , 2019Qiu et al, 2018). Nevertheless, it was found that in viral infection such as IFV, there can be a change in the metabolism of the cells as well as alteration in the ciliary gene expression, mostly in the form of down-regulation of the genes such as dynein axonemal heavy chain 5 (DNAH5) and multiciliate differentiation And DNA synthesis associated cell cycle protein (MCIDAS) (Tan et al, 2018b.…”
Section: Types Of Exacerbation Mechanismmentioning
confidence: 99%